ChemInform Abstract: Stereo‐ and Regioselective Synthesis of Polysubstituted Chiral 1, 4‐Oxazepanes. Issue 25 (3rd June 2013) - Bezanson, Michelle; Pottel, Joshua; Bilbeisi, Rana; Toumieux, Sylvestre; Cueto, Mickael; Moitessier, Nicolas
Abstract An efficient and stereoselective access to the 7‐membered ring system is possible via cyclization of unsaturated amino alcohols.